PERAN AUDIT DALAM TATA KELOLA PERUSAHAAN: STUDI KASUS PADA PT REKADAYA ELEKTRIKA - Putri, Inayah; Miharja, Kasmanto; Angeli, May; Romadhan, Satriya (Universitas Trilogi, 2024)
This research focuses on a case study of the company PT Rekadaya Elektrika and aims to analyze the role of audit in the governance of electrical engineering companies. The research method used is secondary research, which collects data from reliable sources including company data and related literature. This research shows that auditing plays an important role in ensuring the company complies with applicable regulations, increasing transparency, and improving the efficiency and effectiveness of company operations. This study provides detailed insights into how corporate governance can be improved through the implementation of good and proper audit practices.Keywords: Auditor; Internal Auditor; External Auditor; Corporate Governance